TO THINK AFRICA IN THE CLASSROOM EDUCATION, LOGOPATHIC KNOWLEDGE AND AFRICANITIES IN THE FILM BEASTS OF NO NATION - Neto, Humberto Perinelli [UNESP]; Baldacin Junior, Alexandre Cristiano (Centro Univ Nove Julho, 2018)
The text presents an analysis of the film Beasts of no nation to generate their pedagogical appropriation for the development of educational practice focused on the Education of Ethnic-Racial Relations, more specifically the Teaching of African History and Cultures. It is a research with qualitative approach, applied nature and that reconciled description and explanation, using bibliographic and documentary investigations. The interpretation promoted indicates that Bests of no nation is interesting to think about some concepts such as ethnicity, nation, borders, State and them, for understanding African countries. A pedagogical appropriation of this film is pertinent for the elaboration of pedagogical proposals based on decolonial thinking and interculturality.
Keywords: Africanities; Beasts of no Nation; Logopathic Knowledge; Education and cinema; Ethnic-racial relations education